Pengaruh Brand Image, Kualitas Pelayanan dan Price terhadap Loyalitas Tamu pada CV. Betah Banget Corp - Hany Octafiany; Purwatiningsih Purwatiningsih (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to empirically analyze the influence of Brand Image, Service Quality, and  Price on Guest Loyalty in CV Betah Banget Corp, an entity in the accommodation industry that faces fierce competition in the digital era. The quantitative method was used with a multiple linear regression analysis approach to test the relationships between variables. The results of the partial test showed that Brand Image had a significant influence on Guest Loyalty (Count = 2.701 > Ttable = 1.659; sig = 0.008 < 0.05), confirming that positive perception of Brand Image is a key factor in building customer loyalty. Service quality showed a very significant influence (Thcal = 7,338 > Ttable = 1,659; sig = 0.000 < 0.05), strengthening the role of service as a key driver of guest retention amid increasing consumer expectations. In contrast, the  Price variable did not show a significant influence on Guest Loyalty (Thcal = 0.709 < Ttable = 1.659; sig = 0.480 > 0.05), indicating that the  Price aspect is not a major determinant in a customer's decision to remain loyal. These findings provide strategic implications for accommodation industry players to prioritize strengthening Brand Image and improving service quality in an effort to maintain customer loyalty.